FOOD DIVERSIFICATION COMMUNICATION MODEL FROM RICE CONSUMPTION TO TUBER CONSUMPTION - Dewi Widowati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
The mention of Indonesia as a country whose main income is through agriculture, will at least give the impression that Indonesia is truly self-sufficient in food, in other words, it is independent in meeting the food needs of its people. But this is not in accordance with the existing reality. Until now, Indonesia is still dependent on food imports, especially rice commodities, which are still a fairly high order of imported foods. This study aims to analyze the mechanism of food diversification and communication channels built by the community and solve them by using an effective communication model approach. The purpose of this study is to create an effective communication model related to food diversification from rice consumption to tuber consumption. The theory used in the research, namely the Cultural Convergence Theory. This research method uses qualitative descriptive, discussing food diversification in Gunung Putri Village, Kec. Banjar, Kab. Pandeglang. The findings in this study, that the people of Gunung Putri Village, still have not implemented food diversification from consumption of rice to consumption of tubers. Keywords: Diversification, Communication Model, Interaction, Transactional